УСМОН АЗИМ ШЕЪРИЯТИДА ҚАЛБ ҲАРОРАТИ - Исманжонова, Мафтуна Турсунпўлат қизи (INTERNATIONAL CONFERENCES, 2022)
In this article are researched the most used symbols in Usmon Azim poerty? As like ko‘ngil (heart, soul) and sematically intimate words – yurak and qalb.